Engendering Care in the Politics of the East Bengali Refugee Identity: A Reading of Bengal Partition Narratives Through the Lens of Ecological and Culinary Citizenship - Chowdhury, Namrata (Journal of Ecohumanism, 2024)
The ‘politics of care’ has become an essential dialectical discourse within the field of ecofeminism with the intervention of theorist Sherilyn Macgregor. The engendering of care has politicized the figure and the status of the woman within and beyond the domestic space. Further, this discourse has gone beyond the cultural domain of domesticity to realign itself with the understanding of care work in the light of ecological citizenship. In the light of this my paper proposes to revisit South Asian partition historiography to look at the figure of the refugee. I wish to look at the Bengal Partition of 1947 and discern how the East Bengali refugee maneuvers their identity vis-à-vis their claim of ecological and culinary citizenship. Sunanda Sikdar’s novel A Life Long Ago, translated by Anchita Ghatak for Penguin and the recipient of the Ananda Puraskar 2010 award, is a memoir that reproduces the anxieties that are part of the division of Bengal and the subsequent interruption, creation, preservation of the notion of citizenship and the instituting and the drawing of the national border that separates India from Bangladesh, erstwhile East Pakistan. Meanwhile, the anthology edited by Bashabi Fraser, Bengal Partition Stories: An Unclosed Chapter, contains multiple stories that problematize the notion of national borders specifically by challenging these political lines vis-à-vis the culinary code. Through selective stories from the anthology mentioned and Sikdar’s memoir, the paper seeks to address the issue of citizenship and national borders through the realm of the kitchen, food consumption and domesticity and how the gastronomic experience is informed by the ecofeminist rhetoric of the ‘politics of care’. I would also look at Bhaswati Gosh’s debut novel Victory Colony 1950, and Madhushree Ghosh’s culinary memoir Khabaar: An Immigrant Journey of Food, Memory, and Family, which threaten and dismantle the gender binaries embedded within the discourse of care politics.